How do globalization and foreign direct investment affect environmental quality in OIC member countries? - Fatima Farooq; Imran Sharif Chaudhry; Zulkornain Yusop; Muzafar Shah Habibullah (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
The present study explores the effects of globalization and foreign direct investment (FDI) on environmental quality in OIC countries. The main purpose of the study is to analyze that how opening of OIC economies together with inward FDI affect the environmental quality in terms of CO2emissions. In this study, GMM technique has been appliedto address the endogeneity issue in the variables of globalization and foreign direct investment, among others. The results of GMM method of estimation show that globalization and FDI enhance CO2emissions,means lowering environmental quality in overall OIC countries and low-income OIC countries but reduces CO2emissions in high-income OIC countries. Institutional quality, urbanization and industrialization have considerable impact on CO2emissions in overall OIC countries as well as low income and high income OIC countries.The study showed that globalization and foreign direct investment are contributing to improving the environmental quality in high-income OIC states but reduces environmental quality in all OIC states and low-income OIC countries. The present study comes up with the useful information that opening of markets of OIC countries to the world and inward foreign direct investment have very strong influence on the environmental quality and both factors should be used in a way which leads to lowering the level of carbon emissions in OIC states.
Keywords: 330; globalization; FDI; industrialization; environmental quality; institutional quality; governance; CO2 emissions